2016
DOI: 10.1112/plms/pdw038
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Weyl sums, automorphic functions and invariance principles

Abstract: Hardy and Littlewood's approximate functional equation for quadratic Weyl sums (theta sums) provides, by iterative application, a powerful tool for the asymptotic analysis of such sums. The classical Jacobi theta function, on the other hand, satisfies an exact functional equation, and extends to an automorphic function on the Jacobi group. In the present study we construct a related, almost everywhere non-differentiable automorphic function, which approximates quadratic Weyl sums up to an error of order one, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…In this section we describe explicitly the random variable X featured in Theorem 1.1. We refer to §2 of [1] for more details. 2020/10/26 14:18 6 F. Cellarosi…”
Section: The Limiting Random Variable Xmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section we describe explicitly the random variable X featured in Theorem 1.1. We refer to §2 of [1] for more details. 2020/10/26 14:18 6 F. Cellarosi…”
Section: The Limiting Random Variable Xmentioning
confidence: 99%
“…Let ω be the standard symplectic form on R 2 , ω(ξ, ξ ) = x y − yx , where ξ = x y , ξ = x y . The Heisenberg group H(R) is defined as R 2 × R with the multiplication law (ξ, t)(ξ , t ) = ξ + ξ , t + t + 1 2 ω(ξ, ξ ) . (2.8)…”
Section: The Universal Jacobi Group Gmentioning
confidence: 99%
See 1 more Smart Citation
“…More pertinent to the current work, Lehmer showed that Cornu spirals arise from incomplete Gaussian summations [2], which encompass the triangular lacunary trigonometric system of the current work. Berry and Goldberg developed a renormalization procedure for such Cornu spirals [4] as did Sinai [31] and Fedotov and Klopp [32], while Cellarosi and Marklof investigated the related quadratic Weyl summations [33], and Paris provided much insight into various expansions of such systems along with asymptotic behavior [3]. Indeed families of, at times elaborate, combinations of Cornu spirals arise when considering F n,q .…”
Section: Fresnel Integrals and The Cornu Spiralmentioning
confidence: 99%
“…It is well-known that the operators U φ : f → f φ are unitary; note that f π/2 =f . Moreover, Θ f is a smooth function on G (see [5] for example). LetΓ be the subgroup of G defined bỹ…”
Section: Effective Ratner Equidistribution Theoremmentioning
confidence: 99%